O polskiej autonomii narodowo-terytorialnej na Litwie (wiosna – lato 1991 roku) - Sirutavičius, Vladas (Studia z Dziejów Rosji i Europy Środkowo-Wschodniej, 2017)
On the Polish national and territorial autonomy in Lithuania (the Spring–Summer of 1991) Abstract A new system of Polish-Lithuanian relations was shaped manly by the passivity of Poles inhabiting the eastern Lithuania in the plebiscite organised by the Lithuanian government on 9 February 1991, and a decision of the authorities of Vilnius and Šalčininkai (Polish: Sołeczniki) regions to hold a referendum, initiated by Mikhail Gorbachev, on the future of the Soviet Union to turn it into a new, loose confederation of states, which was not recognized by the Lithuanian authorities. Such an attitude of Lithuanian Poles was determined by several factors. Firstly, the Soviet social and economic structure; secondly, for a large part of people the old governments of the Vilnius and Šalčininkai districts and the memory of the Lithuanian Soviet Socialist Republic guaranteed stability and predictability. The soviet structures were more trusted than a newly introduced, not strong yet Lithuanian social and political order. The sense of threat was intensified by an unquestionable domination of Lithuanians on all levels of the new hierarchy. Social and political reforms were perceived by the Polish minority in Lithuania through the prism of a rule of the majority. For the rest of the Lithuanian society (except of the Russian minority) such an attitude was completely incomprehensible. In such complex geopolitical circumstances Poles from the regions of Vilnius and Šalčininkai decided to convene a congress of deputies of the Vilnius and Šalčininkai regions to Mostiškės. According to a project adopted at the Congress, the Vilnius district was to become „an autonomous administrative-territorial unit within the Lithuanian Republic”, with a broad political autonomy. In the opinion of Lithuanians, however, the region of Vilnius should not be “an autonomous administrative-territorial unit of the Lithuanian State”, but form a part of Lithuanian federation. This meant that the Poles wanted to enlarge the status of the Vilnius region and to strengthen its autonomy within Lithuania. The implementation of such a project would mean a decentralisation of the state. In a complex geopolitical situation of that time all attempts at the decentralisation of the country was regarded by the Lithuanian political elite as the threat of the security of the young Lithuanian state, its sovereignty and territorial integrity. О польской национально-территориальной автономии в Литве (весна-лето 1991 г.) Пассивность поляков, живших в Восточной Литве, в плебисците, организованном литовскими властями 9 февраля 1991 и решение властей Виленского и Солечницкого районов организовать референдум о преобразовании Советского Союза в новую, более свободную конфедерацию, объявленный Горбачевым и признанный литовскими властями нелегальным, формировали новую систему польско-литовских отношений. Причины такой позиции литовских поляков были предопределены несколькими обстоятельствами. Во-первых, старой, советской общественно-экономической структурой. Во-вторых, прежними властями Виленского и Солечницкого районов, а также памятью o Литовской ССР, которые для значительной части жителей гарантировали стабильность и предсказуемость. Советские структуры вызывали больше доверия, чем новый, еще не укрепленный, литовский общественный и политический строй. Дополнительно, чувство опасности среди жителей усиливалось из-за подавляющего преобладания литовцев на всех уровнях новой власти. Общественно-политические реформы оценивались представителями польского меньшинства сквозь призму господства большинства. Для остальной части литовского общества (за исключением русского меньшинства) такой подход был совсем непонятен. В настолько сложном геополитическом положении поляки из Виленского и Солечницкого районов решились на созыв съезда депутатов в Мостишках. Согласно, принятому на съезде проекту статус Виленского края был определен как „автономная административно-территориальная единица в составе Литовской Республики ”. Для нее предусматривалась широкая политическая автономия. В свою очередь, согласно литовцам, Виленский край не должен быть автономной административно-территориальной единицей литовского государства, а „государственной единицей” соединенной федеративными узами с Литвой. Это означает, что целью поляков являлось расширение статуса Виленского края и укрепление его автономии по отношению к центральным властям. Осуществление такого проекта означало децентрализацию Литвы. В сложных геополитических условиях этого периода литовские политические элиты истолковывали попытки децентрализации страны как угрозу безопасности молодого литовского государства, его суверенитета и территориальной целостности.